Reconfigurable Intelligent Surface Assisted NOMA for Next-Generation Wireless Communications - Kumar, M Hemanta (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: Reconfigurable Intelligent; Surface Assisted; NOMA for Next-Generation; Wireless Communications